2019
DOI: 10.1021/acsomega.9b01078
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative Particle Dynamics Simulations of a Protein-Directed Self-Assembly of Nanoparticles

Abstract: Design and fabrication of multifunctional porous structures play key roles in the development of high-performance energy storage devices. Our experiments demonstrated that nanostructured porous components, such as electrodes and interlayers, generated from the protein-directed self-assembly of nanoparticles can significantly improve the battery performances. The protein-directed assembly of nanoparticles in solution is a complex process involving the complicated interactions among proteins, particles, and solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…The generated porous structure was an advantage for electrode applications as illustrated in Figure 4c. Besides SP, the same research group [ 49b ] reported that gelatin protein also showed the capability to drive the self‐assembly of CB particles, leading to rational porous structures. Interestingly, it was found that the solvent influenced the self‐assembly process and more optimized porous structure could be obtained in acetic acid/deionized water (AA/DI) solvent (Figure 4d,e).…”
Section: Proteins As Structure‐control Agentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The generated porous structure was an advantage for electrode applications as illustrated in Figure 4c. Besides SP, the same research group [ 49b ] reported that gelatin protein also showed the capability to drive the self‐assembly of CB particles, leading to rational porous structures. Interestingly, it was found that the solvent influenced the self‐assembly process and more optimized porous structure could be obtained in acetic acid/deionized water (AA/DI) solvent (Figure 4d,e).…”
Section: Proteins As Structure‐control Agentsmentioning
confidence: 99%
“…On the contrary, DI treated sample presented a severe coverage of protein on the CB surface (Figure 4f). The researchers [ 49 ] systematically investigated through comprehensive dissipative particle dynamics (DPD) simulations on the self‐assembly process. The solvent environments played key roles in the assembled structure because the solvent changed the distribution of charges on the gelatin side chains.…”
Section: Proteins As Structure‐control Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The calculation of the Flory-Huggins parameters from the individual bead solubilities causes quite a versatile parameterization of the coarse-grained DPD interactions. The DPD method has found an enormous area of application in modeling and simulation of complex soft matter [15] from polymers [16,17] to proteins [18,19]. Nevertheless, the DPD method has employed certain critical assumptions limiting the applicability of the method, one of which is that beads have comparable sizes.…”
Section: Introductionmentioning
confidence: 99%